Knowledge and attitudes of Australian dermatologists towards sentinel lymph node biopsy for melanoma: a mixed methods study. (5th December 2020) - Smith, Andrea L; Watts, Caroline G; Robinson, Samuel; Schmid, Helen; Goumas, Chris; Mar, Victoria J; Thompson, John F; Rapport, Frances; Cust, Anne E
Abstract: Background/Objectives: In melanoma management, sentinel lymph node biopsy (SLNB) is used to stage patients and to indicate prognosis. More recently, it has been used to select patients for adjuvant therapy. This study aimed to report knowledge of and attitudes towards SLNB for patients with melanoma among Australian dermatologists. Methods: Mixed methods study using cross‐sectional questionnaires ( n  = 88) and semi‐structured interviews ( n  = 13), May–September 2019. Results: Of the dermatologists surveyed, 56% thought SLNB had an important role in melanoma management, 26% were unsure and 18% thought SLNB unimportant. Of the 92% who would discuss SLNB with their patients, the main stated value of SLNB was for assessing eligibility for adjuvant therapies (79%); only 60% indicated SLNB was of value for providing prognostic information, and just over half (53%) thought it could improve staging. Interview data indicated that attitudes towards SLNB are shifting among dermatologists, driven by data from landmark clinical trials and the influence of professional networks. Accordingly, interviewees adopted one of three positions in relation to SLNB: (a) believed in utility of SLNB and adhered to the guidelines; (b) were unconvinced about utility of SLNB but adhered to the guidelines; and (c) were unconvinced about utility of SLNB and did not adhere to the guidelines. Conclusion: Although most of the dermatologists surveyed were familiar with and follow the SLNB recommendations, some disagreement with and distrust of the recommendations was evident. Greater acceptance of the SLNB recommendations appeared to be driven by the improved outcomes demonstrated in stage III patients receiving adjuvant systemic therapy.